Reduction of injury rate when introducing automated control systems of production processes at energy enterprises - R. N. Pigilova; F. M. Filippova; Yu. A. Averyanova (Омский научный вестник)
The research examines a number of measures to prevent accidents at industrial enterprises. Therefore, the study of the most likely dangerous and harmful production factors and a statistical analysis of emergency situations in the energy sector of the industry over the past seven years were initially conducted. The research showed that an automated process control system is the most effective tool: it provides operational information about the process, the condition of equipment and controls, significantly reduces non-production costs and energy losses. It is proposed to strengthen the automated process control system by integrating operational dispatch control modules and maintenance of the production process in order to reduce injuries due to the human factor.